Development of a Nonlinear Harvesting Mechanism from Wide Band Vibrations - Md Abdul Halim; Md Momin Hossain; Mst Jesmin Nahar (Association for Scientific Computing Electronics and Engineering (ASCEE), 2022)
The main objective of this study is to present an energy harvesting approach to scavenge electrical energy from mechanically vibrated piezoelectric materials.A mechanical energy harvester device has been developed and tested. The fundamental benefit of this mechanical device is that it can function effectively in a wide range of ambient vibration frequencies, whereas traditional harvesters are limited. A suitable conditioning circuit for energy scavenging has been proposed which can achieve optimal power stream. For controlling the power flow into the battery a circuit has been designed consisting of an AC to DC rectifier, an output capacitor, a switch mode DC to DC converter, and an electromechanical battery. An adaptive control system has been described for switching any electronics devices and maximizing battery storage capacity. Experimental results reveal that the power transfer rate can be enhanced by approximately 400% by utilizing the adaptive DC to DC converter. Various investigations on the piezoelectric harvester have revealed that the energy generated by the mechanical device can exceed the 1.4-volt barrier, which is suitable for charging capacitors in electronics devices. The findings of this study will be crucial in mitigating society's energy crisis.